COMPARATIVE ANALYSIS OF THE EFFICIENCY OF HYBRID AND NON-HYBRID CARS: EFFECT OF WEIGHT, TORQUE AND PRICE - Ikwal, Ahmad; Ginting, Ph.D, Dianta; Witanta, Maulana (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Fuel serves as the primary energy source for motor vehicles, enabling them to move. Although it has been the primary energy source for several centuries, Fuel has led to various environmental issues. One of its negative impacts is that, when burned, Fuel produces carbon dioxide (CO2), a significant contributor to global climate change. Currently, this petroleum-based energy is facing a crisis. Hybrid vehicles present a solution to address this petroleum energy crisis. Recently, hybrid cars have become popular in the modern automotive industry due to their numerous advantages, especially fuel efficiency and emissions. Hybrid vehicle technology combines conventional engine technology that uses Fuel with electric motor technology. This study provides a comprehensive comparative analysis between hybrid and non-hybrid cars, focusing on fuel efficiency, vehicle weight, torque, and price parameters. The aim is to assess the economic feasibility of hybrid vehicles compared to non-hybrid cars. The methodology used is a quantitative comparative study of several hybrid and non-hybrid car models within the same class. Performance data were systematically collected from reliable sources and analyzed under standard conditions, covering various price segments ranging from 600 million to 1.6 billion rupiahs. Statistical analysis was conducted to compare fuel efficiency, torque, and vehicle weight between the two types of cars and evaluate the economic implications of these differences. The study results indicate that hybrid cars achieve significantly higher fuel efficiency, averaging 18–22 km/l, compared to 10–14 km/l for non-hybrid models (p < 0.05). This efficiency increase persists despite increasing torque and vehicle weight, demonstrating that hybrid technology improves performance without sacrificing efficiency. Additionally, cost analysis suggests that although the initial price of hybrid cars is higher, fuel savings can offset the price difference in the long term. This research is expected to serve as a reference for consumers considering cost and energy efficiency when choosing hybrid and non-hybrid cars.